Pengaruh Disiplin, Motivasi Dan Keahlian Kerja Terhadap Kinerja Karyawan PT. Semen Baturaja (Persero) Tbk - Biti Lianti; M. Amirudin Syarif (STIKes Ibnu Sina Ajibarang, 2024)
This research was conducted at PT. Semen Baturaja (Persero) Tbk. The aim of this research is to determine the influence of Work Discipline (X1), Work Motivation (X2) and Work Skills (X3) on Employee Performance (Y) of PT. Semen Baturaja (Persero) Tbk. This study uses a Quantitative Method approach. For data processing methods in this study using smartPLS SEM (Partial Least Square – Strutural Equation Modeling) software. For data analysis used in this research, Outer Model Analysis, Inner Model Analysis and Hypothesis Testing using statistical values, for Alpha 5% the T-Statistics value used is HA accepted and HO, to reject or accept the hypothesis using probability then HA is accepted if the P value <0.05. The data sources used are primary data and secondary data. The data collection technique used is by direct observation, distributing questionnaires (questionnaire). Respondents in this study were 80 respondents to employees of PT. Semen Baturaja (Persero) Tbk. Based on the analysis, it can be concluded that work discipline, work motivation and work skills have a significant effect on employee performance, while partially work discipline, work motivation and work skills have an effect on employee performance. From this research, the r-square value is 0.824, which means that 82.4% of the variation in employee performance is explained by variations in work discipline, work motivation and work skills, while the remaining 17.6% is explained by other factors not examined by this research.